2022
DOI: 10.1002/hed.27113
|View full text |Cite
|
Sign up to set email alerts
|

Association of low skeletal muscle mass and systemic inflammation with surgical complications and survival after microvascular flap reconstruction in patients with head and neck cancer

Abstract: Background: Skeletal muscle mass (SMM) and chronic inflammation are associated with postoperative complications and survival.Methods: Patients with head and neck cancer (HNC) undergoing microvascular free flap reconstruction were included. SMM and neutrophil-to-lymphocyte ratio (NLR) were measured and their association with treatment outcomes analyzed. Results: Five hundred and fifty-four patients were included. Predictors for complications were elevated NLR in all flaps (OR 1.5), low SMM in radial forearm fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 72 publications
1
1
0
Order By: Relevance
“…Similarly, this study found that patients with an MHI less than $55,000 were more likely to experience postoperative complications and unplanned reoperations. This aligns with findings by Chargi et al, 12 who reported that lower SES, often accompanied by comorbidities like low skeletal muscle mass and chronic inflammation, increased the likelihood of complications and negatively impacted survival rates.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, this study found that patients with an MHI less than $55,000 were more likely to experience postoperative complications and unplanned reoperations. This aligns with findings by Chargi et al, 12 who reported that lower SES, often accompanied by comorbidities like low skeletal muscle mass and chronic inflammation, increased the likelihood of complications and negatively impacted survival rates.…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, research on body composition and especially on SMM has increased. It appears that a low SMM is associated with acute and late adverse events in patients with head and neck cancer during (chemo)radiotherapy [ 20 23 ], flap-related complications [ 24 , 25 ], decreased survival rates [ 26 – 29 ], and PCF [ 18 , 19 ]. This emphasizes the importance of considering SMM in assessing PCF risk.…”
Section: Introductionmentioning
confidence: 99%